Global publication trends and research hotspots of curcumin application in tumor: A 20-year bibliometric approach - Zhang, Jun; Huang, Yanran; Xu, Jingtao; Zhao, Runhan; Xiong, Chuang; Habu, Jiwa; Wang, Yuping; Luo, Xiaoji (Frontiers in Oncology, 2022)
Abstract：Malignant tumor is a disease caused by the imbalance of cell growth and proliferation mechanism, which seriously threatens human health and life safety. However, side effects and drug resistance are the key factors that limit the efficacy of anti-tumor drugs. Therefore, it is urgent and necessary to explore and unearth natural, safe and effective chemosensitizers in tumor researches. Curcumin is the main active ingredient in Curcuma, which has anti-inflammatory, anti-inflammatory and anti-oxidation effects, and has inhibitory effects on a variety of cancers. Bibliometric analysis is a scientific and quantitative method to assess the published articles, which can help researchers to find the development trends and the research hotspots of a specific research field, providing the development of future research for researchers. This study searched the Web Science Core Collection (woscc) for publications related to curcumin and tumors from January 1, 2001 to December 31, 2021. The specific characteristics of 1707 publications were analyzed by using Microsoft Excel software, CiteSpace, Vosviewer and online analysis platform of literature metrology. China has had the largest number of published articles, with 579 publications. Aggarwal BB's articles total citations and average citations were the most. PLoS One had the largest number of publications, with 32 publications. The current research focuses on "nanoparticles", "delivery", "micells" and "doxorubicin". At present, nano based drug delivery system to improve the bioavailability of curcumin and thus to treat tumors will be the focus of future research.